Fun-Cooking for Early Childhood in Increasing Creativity for Learning at Home During Covid-19 in West Lombok Regency, West Nusa Tenggara, Indonesia - MA Muazar Habibi (AL-ISHLAH: Jurnal Pendidikan, 2022)
Creative activities cannot be conducted by children freely at home due to COVID-19, a pandemic that shifted the learning system to online. This study aimed to examine the effectiveness of fun-cooking as a strategy for increasing children's creativity through fun cooking. It was conducted on children aged 5-6 years (Early Childhood) in West Lombok, West Nusa Tenggara. A descriptive qualitative method was used through a case study approach. Furthermore, 3 fun cooking menus were used, including fruit satay, layer pudding, and character chocolate. The data was collected using observation instruments. The results showed that each child develops creativity based on 3 categories, including less good (KB), quite good (CB), and good (B). Therefore, fun cooking can increase children's creativity with preparation, implementation, and completion stages.